Recent Advances in Experimental Dendritic Cell Vaccines for Cancer - Filin, Ivan Y.; Kitaeva, Kristina V.; Rutland, Catrin S.; Rizvanov, Albert A.; Solovyeva, Valeriya V. (Frontiers in Oncology, 2021)
The development of immunotherapeutic methods for the treatment of oncological diseases have made it possible to improve the effectiveness of standard therapies. The first use of personalized therapeutic vaccines based on dendritic cells did not ‘make a splash’ in clinical practice. A deeper study of the biology of dendritic cells, as well as the use of new approaches and agents for antigenic work, have made it possible to expand the field of application of dendritic vaccines and improve the indicators of cancer patients. In addition, the low toxicity of dendritic vaccines in clinical trials makes it possible to use promising predictions of their applicability in wider clinical practice. This review examines new approaches and recent advances of the dendritic vaccine in clinical applications.